A mobile teaching value chain framework / Siti Zulaiha Shabirin - Shabirin, Siti Zulaiha (2017)
Currently, there is no existing of systematic adoption of mobile teaching, which may leads to a mismatch of capabilities and needs of specific target lecturers and students in higher education. In addition, there are problems of sustainability and under-utilization of mobile teaching occurs due to the technology and requirement mismatch. The main objectives of this study are (i) to investigate the elements to adopt mobile teaching value chain framework for the mobile teaching in UiTM and (ii) to design the mobile teaching value chain framework. Qualitative open-ended questions responses were gathered from lecturers in Universiti Teknologi MARA. The open ended questionnaires responses to provide empirical evidence to support the proposed mobile teaching value chain framework. Qualitative Content Analysis Method was used in this study. The analysis of the qualitative content analysis method provides (i) qualitative results for this study to unravel the elements to adopt mobile teaching value chain framework (ii) qualitative results for designing the mobile teaching values chain framework. The qualitative results were into six themes, (i) Elements need to be included in the mobile teaching value chain framework, (ii) Factors to use mobile teaching, (iii) Example of mobile teaching, (iv) Advantages of using mobile teaching, (v) Challenges of using mobile teaching, and (vi) Important to have a framework to guide the adoption of mobile teaching are to provide empirical support the mobile teaching value chain framework. Future work may involves actual implementation of the framework for lecturers who may want to adopt the Mobile Teaching Value Chain Framework as guidance.